The role of textile production and fishing in the EBA metallurgical centre of Çukuriçi Höyük (Turkey) - Britsch, Christopher (Ägypten und Levante, 2014)
A large number of ovens combined with metallurgical equipment and slag from the Early Bronze Age settlement of Çukuriçi Höyük allows classifying the settlement as a metallurgical center. The wide range of other tools, however, show that a lot of different crafts where performed alongside the metal production. Two of these activities-textile production and fishing-are easily traceable via ceramic small finds and faunal remains. Both textile production and fishing are time consuming activities. This paper analyzes to which extent these crafts were performed and therefore how they were organized and embedded in the specialized society of Çukuriçi Höyük.